Real-world disparities and ethical considerations with access to CFTR modulator drugs: Mind the gap! - Zampoli, M.; Morrow, B. M; Paul, G (Frontiers in Pharmacology, 2023)
The third United Nations Sustainable Development Goal (SDG), to ensure healthy lives and promote well-being for all has particular relevance amongst people living with rare diseases such as cystic fibrosis (CF) .Although the treatment and projected outcome of CF has significantly improved with the advent of CF transmembrane regulator protein modulator therapy (CFTRm), there is significant global inequality in access to these life-saving drugs. Highly effective CFTRm, first licensed in the United States in 2019, has rapidly become the standard of care for children six years and older in most high-income countries for individuals with CFTRm responsive variants. Negotiated agreements for access to CFTRm drugs are in currently in place in North America, Western Europe, and Australia. However, there has been little progress in negotiating agreements for access to CFTRm in low-middle income regions (LMIC) such as Central and South America, India, the Middle East, and Southern Africa. In this review we highlight the inequity in access to CFTRm drugs and what impact this has on widening disparities between high and LMICs in CF outcomes . We further discuss the reasons for this inequity and explore the ethical and human rights- based principles and dilemmas that must considered when prioritising fair and affordable access to expensive CFTRm drugs. Lastly, we propose solutions to overcoming the barriers to accessing affordable CFTRm therapies in LMIC and illustrate with examples how access to drug therapies for other conditions have been successfully negotiated in LMIC through innovative partnerships between governments and pharmaceutical industries.